Surgical resection of early stage hepatocellular carcinoma improves patient survival at safety net hospitals. Issue 4 (26th January 2021) - Vitiello, Gerardo A.; Wang, Annie; Lee, Rachel M.; Russell, Maria C.; Yopp, Adam; Ryon, Emily L.; Goel, Neha; Luu, Sommer; Hsu, Cary; Silberfein, Eric; Correa‐Gallego, Camilo; Berman, Russell S.; et al.
Abstract: Background and Objectives: Surgical resection is indicated for hepatocellular carcinoma (HCC) patients with Child A cirrhosis. We hypothesize that surgical intervention and survival are limited by advanced HCC presentation at safety net hospitals (SNHs) versus academic medical centers (AMCs). Methods: Patients with HCC and Child A cirrhosis in the US Safety Net Collaborative (2012–2014) were evaluated. Demographics, clinicopathologic features, operative characteristics, and outcomes were compared between SNHs and AMCs. Liver transplantation was excluded. Kaplan–Meier and Cox proportional‐hazards models were used to identify the effect of surgery on overall (OS). Results: A total of 689 Child A patients with HCC were identified. SNH patients frequently presented with T3/T4 stage (35% vs. 24%) and metastases (17% vs. 8%; p  < .05). SNH patients were as likely to undergo surgery as AMC patients (17% vs. 18%); however, SNH patients were younger (56 vs. 64 years), underwent minor hepatectomy (65% vs. 38%), and frequently harbored well‐differentiated tumors (23% vs. 2%; p  < .05). On multivariate analysis, surgical resection and stage, but not hospital type, were associated with improved OS. Conclusions: Although SNH patients present with advanced HCC, survival outcomes for early stage HCC are similar at SNHs and AMCs. Identifying barriers to early diagnosis at SNH may increase surgical candidacy and improve outcomes.